Essential role of carbonic anhydrase XII in secretory gland fluid and HCO3− secretion revealed by disease causing human mutation. (7th December 2015) - Hong, Jeong Hee; Muhammad, Emad; Zheng, Changyu; Hershkovitz, Eli; Alkrinawi, Soliman; Loewenthal, Neta; Parvari, Ruti; Muallem, Shmuel
Abstract : Key points: Fluid and HCO3 − secretion is essential for all epithelia; aberrant secretion is associated with several diseases. Carbonic anhydrase XII (CA12) is the key carbonic anhydrase in epithelial fluid and HCO3 − secretion and works by activating the ductal Cl − –HCO3 − exchanger AE2. Delivery of CA12 to salivary glands increases salivation in mice and of the human mutation CA12(E143K) markedly inhibits it. The human mutation CA12(E143K) causes disease due to aberrant CA12 glycosylation, and misfolding resulting in loss of AE2 activity. Abstract: Aberrant epithelial fluid and HCO3 − secretion is associated with many diseases. The activity of HCO3 − transporters depends of HCO3 − availability that is determined by carbonic anhydrases (CAs). Which CAs are essential for epithelial function is unknown. CA12 stands out since the CA12(E143K) mutation causes salt wasting in sweat and dehydration in humans. Here, we report that expression of CA12 and of CA12(E143K) in mice salivary glands respectively increased and prominently inhibited ductal fluid secretion and salivation in vivo . CA12 markedly increases the activity and is the major HCO3 − supplier of ductal Cl − –HCO3 − exchanger AE2, but not of NBCe1‐B. The E143K mutation alters CA12 glycosylation at N28 and N80, resulting in retention of the basolateral CA12 in the ER. Knockdown of AE2 and of CA12 inhibited pancreatic and salivary gland ductal AE2 activity and fluid secretion. Accordingly, patients homozygous for the CA12(E143K) mutation have a dry mouth, dry tongue phenotype. These findings reveal an unsuspected prominent role of CA12 in epithelial function, explain the disease and call for caution in the use of CA12 inhibitors in cancer treatment. Key points: Fluid and HCO3 − secretion is essential for all epithelia; aberrant secretion is associated with several diseases. Carbonic anhydrase XII (CA12) is the key carbonic anhydrase in epithelial fluid and HCO3 − secretion and works by activating the ductal Cl − –HCO3 − exchanger AE2. Delivery of CA12 to salivary glands increases salivation in mice and of the human mutation CA12(E143K) markedly inhibits it. The human mutation CA12(E143K) causes disease due to aberrant CA12 glycosylation, and misfolding resulting in loss of AE2 activity.